A Novel Putative Role of TNK1 in Atherosclerotic Inflammation Implicating the Tyk2/STAT1 Pathway. (10th July 2020) - Bao, Mei-Hua; Lv, Qiao-Li; Li, Hai-Gang; Zhang, Yi-Wen; Xu, Bao-Feng; He, Bin-Sheng
Abstract : Objective . Atherosclerosis is a chronic inflammatory disease which is responsible for many clinical manifestations. The present study was to investigate the anti-inflammatory functions and mechanisms of TNK1 in atherosclerosis. Methods . The ApoE(-/-) mice and human carotid endarterectomy (CEA) atherosclerotic plaques were used to investigate the differential expression of TNK1. The ApoE(-/-) mice were fed with high-fat diet (HFD) or normal-fat diet (NFD) for 8 weeks; the aorta was separated and stained with oil red O to evaluate the formation of atherosclerosis. TNK1 in mice aorta was measured by qPCR. The human CEA were obtained and identified as ruptured and stable plaques. The level of TNK1 was measured by qPCR and Western-blot staining. Further studies were conducted in THP-1 cells to explore the anti-inflammatory effects of TNK1. We induced the formation of macrophages by incubating THP-1 cells with PMA (phorbol 12-myristate 13-acetate). Afterwards, oxidized low-density lipoprotein (oxLDL) was used to stimulate the inflammation, and the secretion of inflammatory factors was measured by ELISA and qPCR. The levels of TNK1, total STAT1 and Tyk2, and the phosphorylation of STAT1 and Tyk2 were measured by western blot to uncover the mechanisms of TNK1. Results . The oil red O staining indicated obvious deposition of lipid on the aorta of ApoE(-/-) mice after 8-week HFD treatment. The TNK1 level was much higher in both the HFD-fed ApoE(-/-) mice aorta arch and the ruptured human CEA plaques. We found that TNK1 was highly expressed in THP-1 cells, compared to other atherosclerotic related cells (HUVEC, HBMEC, and HA-VSMC), indicating TNK1 might be involved in the inflammation. Suppressing the expression of TNK1 by shTNK1 inhibited the oxLDL-induced secretion of inflammatory factors, such as IL-12, IL-6, and TNF- α . ShTNK1 also inhibited the uptake of lipid and decreased the cellular cholesterol content in THP-1 cells. Furthermore, the shTNK1 suppressed the oxLDL-induced phosphorylation of Tyk2 and STAT1. Conclusion . TNK1 participated in the inflammation in atherosclerosis. shTNK1 suppressed the oxLDL-induced inflammation and lipid deposition in THP-1 cells. The mechanism might be related to the Tyk2/STAT signal pathway.